Zastosowanie taksonomii rozmytej do oceny atrakcyjności inwestycyjnej wybranych spółek giełdowych - Majewski, Sebastian (Using Fuzzy Clustering for Classification of Stocks by Investment Attractiveness Criteria, 2005)
The investment attractiveness of stocks was described by the value of the membership function, which means a degree of belief that pointed stock belongs to the one of three sets: "attractive" stocks, "non-attractive" stocks and stocks from the uncertain area. The analysis was based on two-dimensional and seven-dimensional characteristics of objects. The weekly data from 2002 year were used in the research. The fuzzy c-means method was used to classification of stocks. In the case of using fuzzy clustering for classification of stocks investor has more comfortable information to making investment decisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 537-546